Development of a Biomass Anila Furnace with a casing for preheating - Yusril, Yusril; Sugati, Daru; Salim, Amat Agus (Politeknik Negeri Semarang, 2024)
This study aims to find out the effect of using a shroud mounted on an anila biomass gasification furnace. The casing functions as a guide and heats the air that will enter the combustion chamber. The method used in this study is an experimental method. The type of furnace used in the experiment is a biomass anila furnace. This furnace is made of metal. The casing is attached to the outside and envelops the furnace. Measurements made between long flame, starting time, and flame stability. The test results show that the average startup time is 10 minutes. long flame flame with cover is 87.79 minutes, while without cover is 72.28 minutes. The stability of the flame using the casing is more stable than without the casing.